2011
DOI: 10.1371/journal.pone.0026344
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hERG Potassium Channels by Celecoxib and Its Mechanism

Abstract: BackgroundCelecoxib (Celebrex), a widely prescribed selective inhibitor of cyclooxygenase-2, can modulate ion channels independently of cyclooxygenase inhibition. Clinically relevant concentrations of celecoxib can affect ionic currents and alter functioning of neurons and myocytes. In particular, inhibition of Kv2.1 channels by celecoxib leads to arrhythmic beating of Drosophila heart and of rat heart cells in culture. However, the spectrum of ion channels involved in human cardiac excitability differs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…For example, the voltage-gated sodium channel in rat retinal neurons [11] and dorsal root ganglia (DRG) neurons [12], [13], the L-type calcium channel in rat pheochromocytoma (PC12) cells [14] and A7r5 rat aortic smooth muscle cells [15], Kv2.1 channels expressed in HEK293 cells [16], cardiac Kv1.5, Kv4.3 and Kv7.1 channels in guinea pig cardiomyocytes [17] and human eag-related gene (HERG) potassium channels [18] were all reported to be inhibited by CXB. In contrast, Kv7.5 currents in rat A7r5 aortic smooth muscle cells can be acutely augmented by CXB [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the voltage-gated sodium channel in rat retinal neurons [11] and dorsal root ganglia (DRG) neurons [12], [13], the L-type calcium channel in rat pheochromocytoma (PC12) cells [14] and A7r5 rat aortic smooth muscle cells [15], Kv2.1 channels expressed in HEK293 cells [16], cardiac Kv1.5, Kv4.3 and Kv7.1 channels in guinea pig cardiomyocytes [17] and human eag-related gene (HERG) potassium channels [18] were all reported to be inhibited by CXB. In contrast, Kv7.5 currents in rat A7r5 aortic smooth muscle cells can be acutely augmented by CXB [15].…”
Section: Introductionmentioning
confidence: 99%
“…They include several voltage‐activated ion channels, which are modulated by celecoxib. For example, Na + currents (Park et al , ; Frolov et al , ), L‐type calcium channels (Zhang et al , ; Brueggemann et al , ), Kv2.1 (Frolov et al , ), Kv1.5, Kv4.3 and Kv7.1 (Macias et al , ) and human eag‐related gene potassium channels (Frolov et al , ) are all inhibited by celecoxib. In contrast, celecoxib increases Kv7.2‐5 currents (Brueggemann et al , ; Du et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore,w e observed that celecoxib blocked both hERG potassium channels [IC 50 = 45 mm, K B = 31 mm ;r eference:t erfenadine (K i = 20 nm)] and voltage-gated Na + (site 2) channels (79 % displacement of the channel activator veratrine by 50 mm celecoxib), thereby resolving partially conflicting reports in the scientific literature. [25,37] Many of the identified affinities are within the same order of magnitude of COX-2 inhibition by celecoxib.O ne might therefore regard celecoxib as a" promiscuous drug", in particular when considering its ability to block cardiac hERG and Na + channels and antagonize b-adrenergic receptors in vitro. [37] Nonselective orexin receptor interactions might increase the reported risk of sleep disorders.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…[25,37] Many of the identified affinities are within the same order of magnitude of COX-2 inhibition by celecoxib.O ne might therefore regard celecoxib as a" promiscuous drug", in particular when considering its ability to block cardiac hERG and Na + channels and antagonize b-adrenergic receptors in vitro. [37] Nonselective orexin receptor interactions might increase the reported risk of sleep disorders. [38] Under the assumption of appropriate pharmacokinetics,these target activities could partially explain some of the clinical observations of cardiovascular incidents after taking medication.…”
Section: Angewandte Chemiementioning
confidence: 99%